2008
DOI: 10.1007/s11094-009-0187-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antiviral activity of 4-quinolinecarboxylic acid hydrazides

Abstract: Antiviral agents were sought by using ethyl esters of 2-R-4-quinolinecarboxylic acids to synthesize the corresponding aryl (heteryl) hydrazides. 2-Methyl-4-quinolinecarboxylic acid hydrazide was used to synthesize vinylogs containing a nitro group in the substituent. The resulting compounds were tested for antiviral activity against ECHO virus type 6. 571 0091-150X/08/4210-0571

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…The quinoline scaffold is prevalent in a variety of pharmacologically active synthetic and natural compounds 1. Over the past two decades, functionalized quinolines and benzo‐/hetero‐fused quinolines have attracted much attention due to their considerable biological and pharmacological activities, such as use as antimalarial,2 antiasthmatic,3 antibacterial,4 antiviral,5 anti‐inflammatory,6 antitumor agents,7 potential HIV‐integrase inhibitors,8 and as potent melanin‐concentrating hormone 1 receptor (MCH1R) antagonists 9. Among them, 2 H ‐thiopyrano[2,3‐ b ]quinolines are tricyclic ring systems containing a thiopyran moiety condensed with a quinoline nucleus, and are currently found to be associated with some interesting bioactivities.…”
Section: Catalyst Screening[a]mentioning
confidence: 99%
“…The quinoline scaffold is prevalent in a variety of pharmacologically active synthetic and natural compounds 1. Over the past two decades, functionalized quinolines and benzo‐/hetero‐fused quinolines have attracted much attention due to their considerable biological and pharmacological activities, such as use as antimalarial,2 antiasthmatic,3 antibacterial,4 antiviral,5 anti‐inflammatory,6 antitumor agents,7 potential HIV‐integrase inhibitors,8 and as potent melanin‐concentrating hormone 1 receptor (MCH1R) antagonists 9. Among them, 2 H ‐thiopyrano[2,3‐ b ]quinolines are tricyclic ring systems containing a thiopyran moiety condensed with a quinoline nucleus, and are currently found to be associated with some interesting bioactivities.…”
Section: Catalyst Screening[a]mentioning
confidence: 99%
“…Besides fluoroquinolone-based drugs, 2-chloroquinoline-3-carbaldehyde derivatives have also attracted much attention due to their considerable biological and pharmacological activities including antimicrobial [8], anti-inflammatory [11][12][13], antimalarial [14,15], anticancer [16], antiviral [17,18], and antifungal activities [19,20]. Inspired by these reports, we have designed and synthesized various quinoline-3-carbaldehyde derivatives and evaluated their antibacterial and radical scavenging activities.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results, as listed in Table 4, revealed that the electronic nature and the substitution pattern of 2-mercaptoquinoline-3-carbaldehyde (1) had minimal impact on the efficiency and enantioselectivity of the Michael/aldol reaction ( Table 4, entries [1][2][3][4][5][6][7][8][9][10][11][12]. The experimental results, as listed in Table 4, revealed that the electronic nature and the substitution pattern of 2-mercaptoquinoline-3-carbaldehyde (1) had minimal impact on the efficiency and enantioselectivity of the Michael/aldol reaction ( Table 4, entries [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Compounds that possess these types of ring systems have demonstrated interesting bioactivities. [10] Therefore, it is not surprising that many methods have been developed for their synthesis, for A survey of nine acidic co-catalysts revealed that they play a definite role in governing the reaction yields and enantioselectivities (Table 2, entries [1][2][3][4][5][6][7][8][9]. The use of trifluoroacetic acid as a co-catalyst resulted in a very sluggish reaction, which may be attributed to its strong acidity (Table 2, entry 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation